Biocontrol ability and putative mode of action of yeasts against Geotrichum citri-aurantii in citrus fruit - Ferraz, Luriany Pompeo [UNESP]; Cunha, Tatiane da [UNESP]; Silva, Aline Caroline da; Kupper, Katia Cristina [UNESP] (Elsevier B.V., 2016)
Sour rot is a major postharvest disease of citrus fruit and is caused by the fungal pathogen Geotrichum citri-aurantii. A lack of chemicals certified for the control of this disease has led to the consideration of alternative methods and strategies, such as the use of yeasts as biocontrol agents. The purpose of the present study was to test the ability of yeasts isolated from-leaves, flowers, fruit, and soil, and six Saccharomyces cerevisiae isolates to control citrus sour rot, to assess the mechanisms of action of the yeast isolates that were demonstrated to be effective for biocontrol, and to identify the most effective yeast isolates for the biocontrol of G. citri-aurantii. In in vivo assays, three yeast isolates (ACBL-23, ACBL-44, and ACBL-77) showed a potential for controlling sour rot in citrus fruits, both preventatively and curatively. Most of the eight yeast isolates that were assessed for a mechanism of action did not produce antifungal compounds in an amount sufficient to inhibit the growth of the pathogen. Additionally, nutrient competition among the yeast strains was not found to be a biocontrol strategy. Instead, killer activity and hydrolytic enzyme production were identified as the major mechanisms involved in the biocontrol activity of the yeasts. Isolates ACBL-23, ACBL-44, and ACBL-77, which controlled sour rot most effectively, were identified as Rhodotorula minuta, Candida azyma, and Aureobasidium pullulans, respectively. To our knowledge, this is the first report of the potential of C. azyma as a biological control agent against a postharvest pathogen and its ability to produce a killer toxin. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Citrus spp.; Hydrolytic enzymes; Killer factor; Sour rot